Impact assessment of photovoltaic panels with life cycle analysis techniques - Nikolaos Skarkos; Anthoula Menti; Konstantinos Kalkanis; Ioannis Chronis; Constantinos S. Psomopoulos (Sustainable Futures)
Photovoltaic (PV) technologies are developing rapidly as a result of their ability to reduce energy consumption from conventional sources as well as the growth of global energy expenditures. Nevertheless, several impact categories during the PV panel life cycle occur and some principal sectors are affected. These impact categories are assessed by applying life cycle analysis (LCA) techniques through various software programs, databases and methods. Such analyses of energy technologies are crucial, as they can reveal the occurrence of hazardous emissions at distinct life cycle stages. In the present paper, a PV panel impact assessment through life cycle analysis is carried out. More precisely, a combination of PV technologies—monocrystalline silicon (mono-Si), multicrystalline silicon (multi-Si), cadmium telluride (CdTe), copper indium gallium selenide (CIGS), amorphous silicon (a-Si), and ribbon silicon (ribbon-Si)—is studied, by means of a system configuration retrieved from the Global LCA Data Access (GLAD) network. The impact categories of ozone depletion, human toxicity, particulate matter, ionizing radiation, photochemical ozone formation, acidification, eutrophication, and ecotoxicity, as well as the sectors of human health, ecosystem quality, and environment, are assessed using the openLCA software, the ecoinvent database, the eco-indicator 99, IMPACT 2002+, ReCiPe, and TRACI methods.